Statewide Evaluation of the California Medical Supervision Program Using Cholinesterase Electronic Laboratory Reporting Data: An Update - Stephanie Hung MS; Ouahiba Laribi PhD (SAGE Publishing, 2022)
The California Medical Supervision Program is designed to protect agricultural workers from overexposure to Toxicity Category I and II organophosphate (OP) and carbamate (CB) pesticides by routinely monitoring their blood cholinesterase (ChE) activity levels. ChE testing is conducted at State-approved laboratories and electronically reported to the Department of Pesticide Regulation (DPR) and the Office of Environmental Health Hazard Assessment (OEHHA) for review. In 2015, OEHHA and DPR evaluated the effectiveness of the Program by analyzing ChE data from pesticide handlers performed between 2011 and 2013, which revealed issues with the data quality that hindered the evaluation process. Several interventions have been implemented since then to improve data quality and the overall function of the Program. A new evaluation was conducted in 2020 to 2021 using data from 2014 to 2019 to determine the effectiveness of the Program, Program compliance, and efficacy of the interventions. The analysis revealed similar data quality issues identified in the last evaluation, however, an improvement in data quality was observed. The number of individuals with ChE depression below the action level threshold have decreased in recent years, corresponding to the implementation of certain interventions, indicating that the effectiveness of the Program has improved. Spatial and temporal analysis showed the proportion of pre-exposure baseline tests inversely correlated with pesticide use data while routine follow-up ChE test results showed a positive correlation, indicating a high degree of Program compliance across the state. Major improvements in the data cleaning and analysis since the last evaluation have also improved the evaluation: pesticide handlers under the Program were able to be identified with more certainty and ChE depressions were able to be calculated with increased accuracy. However, further improvements to the data collection process could enhance future evaluations of the Program.